INTEGRATING CHARACTER BUILDING INTO ENGLISH TEACHING AND LEARNING PRACTICE IN INDONESIAN CLASSROOM - Nanik Retnowati (ENGLISH, 2020)
Indonesian government has just made great changes in its national curriculum. One of its changes is the emphasis on character building. For Indonesian teachers, this new policy is quite a challenge. In previous curriculum, character building was treated as a hidden curriculum and not explicitly part of scoring system. The new curriculum explicitly states the characters which must be developed by teachers.  Finding the basis to perform teaching process to achieve the improvement of language knowledge, skills and characters is indeed needed.  An action research was then conducted. In one cycle, the research proved that the implementation of actions  integrating character building into teaching and learning process could significantly improve not only students’ attitude but also their knowledge and skill on expressing things happening in English.  It means that teachers can work on the three important aspects; namely attitude, knowledge and skill together. In other words, teachers could kill two birds with one stone.